A method to predict the radial runout of outer ring in cylindrical roller bearings. (November 2017) - Yu, Yongjian; Chen, Guoding; Li, Jishun; Xue, Yujun
For the rotary motion of a rolling bearing implemented by bearing components under geometric constraints, the rotational accuracy of assembled bearing should also be the result of interaction among geometric errors of bearing components. Therefore, it is significant to research the relationship between geometric errors of bearing components and rotational accuracy of assembled bearing for the design and prediction of bearing accuracy. An accuracy prediction method is proposed to study how the geometric errors of bearing components affect the radial runout of outer ring of cylindrical roller bearings in this article. Furthermore, the calculation model for the orbit of outer ring center is established from which the radial runout of outer ring can be predicted while dimension and roundness errors of raceways and rollers are given arbitrarily. Theoretical algorithms with two typical shapes of outer raceway are deduced to verify the prediction method. In addition, a test on the radial runout of outer ring in a cylindrical roller bearing is performed. The results indicate that prediction results are in good agreement with experimental and analytical results.